Anisotropy of Magnetic Susceptibility (AMS) Analysis of the Gonjo Basin as an Independent Constraint to Date Tibetan Shortening Pulses. Issue 8 (22nd April 2020) - Li, Shihu; van Hinsbergen, Douwe J. J.; Shen, Zhongshan; Najman, Yani; Deng, Chenglong; Zhu, Rixiang
Abstract: The Tibetan Plateau accommodated major upper crustal shortening during Indian Plate oceanic and continental lithosphere subduction. Deciphering whether shortening was continuous or episodic, and how it correlates to major geodynamic changes is challenging. Here we apply anisotropy of magnetic susceptibility (AMS), a sensitive synsedimentary strain indicator, to a ~3 km thick magnetostratigraphically dated sedimentary section (69–41.5 Ma) in eastern Tibet. AMS shows "earliest deformation" fabrics from 69–52 Ma, followed by a sudden change to "pencil structure" fabrics with increasing anisotropy degree at ~52 Ma, dating a sudden increased synsedimentary shortening strain. This change coincides with enhanced sedimentation rates and synsedimentary vertical‐axis rotations of the Gonjo Basin, suggesting a causal link to a marked India‐Asia convergence rate deceleration. We show that AMS analysis provides a strong tool to distinguish between climatic and tectonic causes of sedimentological change and is an asset in identifying discrete tectonic pulses in intensely deformed terrane. Plain Language Summary: How the Tibetan Plateau evolved during India‐Asia convergence and collision is notoriously challenging to decipher. Use of sedimentary records to date periods of tectonic activity is a popular approach, yet distinguishing between tectonic versus climate signals in sediment records can be challenging. The anisotropy of magnetic susceptibility (AMS) is an effective and sensitive technique that reveals tectonic stress fields during sedimentation and changes therein, even in weakly deformed clastic sedimentary rocks. We report a detailed record of AMS data from a ~3 km thick section of redbeds from the Gonjo Basin in eastern Tibet. Previous magnetostratigraphy dated deposition from 69 to 41.5 Ma; during this time period marked sedimentation rate increases and simultaneous vertical‐axis rotations were interpreted to reflect shortening pulses. Our new AMS data indicate an increased shortening strain at ~52 Ma, demonstrating that the sedimentation rate changes are tectonic rather than climatic in origin, showing that a pulse in crustal shortening of Tibet occurred simultaneous with a marked ~52 Ma onset of deceleration of India‐Asia convergence. We show that applying a suite of paleomagnetic and rock magnetic techniques, including magnetostratigraphy and sedimentation rate calculation, vertical‐axis rotation analysis, and AMS analysis, provides a powerful tool to differentiate tectonic versus climatic influence on a sediment archive, allowing the precise dating of discrete deformation phases in intensely deformed regions that evolved over long periods of time. Key Points: The AMS of the Gonjo Basin records sedimentary fabrics overprinted by weak shortening The AMS of the Gonjo Basin indicates an increased strain related to shortening at ~52 Ma AMS with precise age constraint provides a powerful tool to date deformation phases, allowing discrimination between tectonic versus climatic influences on sediments